Rigid/flexible molecular structure‐induced polyimide aerogels with ultralow permittivity and thermal insulation properties - Xiaodi Dong; Baoquan Wan; Lin Qiu; Ming‐Sheng Zheng; Jiefeng Gao; Jun‐Wei Zha (IET Nanodielectrics, 2023)
Abstract A series of high‐performance linear and cross‐linked polyimide (PI) aerogels with different molecular structures have been successfully synthesised using the freeze‐drying process. In this study, the comprehensive regulation of microstructure, thermodynamic, thermal insulation and dielectric properties of PI aerogels are achieved by controlling the rigid/flexible structure and composition of polymerised monomers. The increase in rigidity of PI molecular structure could promote the formation of denser pores, which is beneficial to improve the thermodynamic and thermal insulation properties of aerogels. Notably, the cross‐linked PI aerogel prepared by introducing cross‐linking agent (tris(4‐aminophenyl) amine, [TPA]) into linear PI exhibits high thermal stability (Td5% > 560°C), excellent ultralow permittivity (εr = 1.31, f = 106 Hz) and good thermal insulation property (k = 0.056 W/m · K). This innovative strategy promotes the wider application of the cross‐linked polyimide aerogel in the field of integrated circuits and aerospace exploration.